Information-theoretic measures of ecosystem change, sustainability, and resilience. (19th June 2019) - Boschetti, Fabio; Prunera, Karine; Vanderklift, Mathew A; Thomson, Damian P; Babcock, Russell C; Doropoulos, Christopher; Cresswell, Anna; Lozano-Montes, Hector
Abstract: We introduce five measures describing the system-wide behaviour of complex ecological systems. Within an information-theoretic framework, these measures account for changes in both species diversity and total biomass to describe (i) overall system change, (ii) sustainability to external pressure, (iii) shift from a baseline state and two types of resilience: (iv) ability to recover from local pressures and (v) overall potential to return to a baseline state. We apply these measures to study the behaviour of three computer models: a large 59-functional groups complex ecological model (Ecopath with Ecosim) of north Western Australia undergoing internal dynamics, a smaller 6-group coral reef model subjected to various combinations of single and multiple stressors and a prey–predator model displaying limit cycles. We demonstrate the state-dependency of properties like resilience and sustainability by showing how these measures change in time as a function of internal dynamics and external forcing. Furthermore, we show how our proposed measures can simplify system analysis and monitoring by providing indicators of changes in system behaviour, sustainability, and resilience.